2014
DOI: 10.1016/j.fertnstert.2014.07.1250
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing cryopreservation of human spermatogonial stem cells: comparing the effectiveness of testicular tissue and single cell suspension cryopreservation

Abstract: Objective To determine whether optimal human spermatogonial stem cell (SSC) cryopreservation is best achieved with testicular tissue or single cell suspension cryopreservation. This study compares the effectiveness between these two approaches by using testicular SSEA-4+ cells, a known population containing SSCs. Design In vitro human testicular tissues. Setting Academic research unit. Patients Adult testicular tissues (n = 4) collected from subjects with normal spermatogenesis and normal fetal testicula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 40 publications
0
19
0
1
Order By: Relevance
“…Pacchiarotti et al . (2013) and Yango et al . (2014) stated that TT cryopreservation should be recommended.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Pacchiarotti et al . (2013) and Yango et al . (2014) stated that TT cryopreservation should be recommended.…”
Section: Resultsmentioning
confidence: 98%
“…2007, (2012)HumanMature1.5 M DMSO + 0.15 M sucrose + 10% HSAInsulated container in −80°C, LN2Maintenance of tissue integrity, preservation of cell dynamics in propagation cultureBaert et al . (2013), (2015)1.28 M DMSO + 25% FBSInsulated container in −80°C, LN2Preservation of SSCsYango et al . (2014)VitrificationMouseImmature2.8 M DMSO + 2.8 M EG + 25% HSAStraw, LN2Maintenance of tissue integrity and activity in organotypic tissue cultureCuraba et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies tested this question directly on human samples. Yango and colleagues reported that recovery of SSEA4 + cells from cryopreserved fetal testicular tissue was similar to cryopreserved testicular cells, but recovery of SSEA4 + cells from cryopreserved adult testicular cells was greater than cryopreserved testicular tissue [ 142 ]. Pacchiarotti and coworkers reported that cryopreservation of testicular tissue was comparable in most aspects to cryopreservation of a cell suspension, except the viability of cells from the cryopreserved tissue was higher.…”
Section: Cryopreserving Testicular Tissue or Cellsmentioning
confidence: 99%